Predictors of Female Sexual Aggression Among a U.S. MTurk Sample: The Protective Role of Sexual Assertiveness - Struckman-Johnson, Cindy (Journal of contemporary criminal justice, 2020)
We studied predictors of female sexual aggression (FSA) among a U.S. Mechanical Turk sample (from Amazon’s online crowdsourcing platform) of 634 adult women (median age = 32). A logistic regression analysis revealed that five measures contributed significantly to a model predicting past use of a tactic of post-refusal sexual persistence (PRSP), accounting for 19% of variance. Women’s use of a PRSP tactic was associated with lower scores on two sexual assertiveness measures (the ability to refuse sex and the ability to ask questions about a partner’s sexual health history) and higher scores on measures of acceptance of heterosexual male rape myths, early courtship rehearsal (number of others called, texted, tweeted, sexted due to attraction before the age of 18), and sexual sensation seeking. Based on our results, we suggest that sexual assertiveness training may be a useful addition to anti-sexual assault programming. For better prediction and potential prevention of FSA, we recommend continued research on the variables in this study and additional factors related to maladaptive personality (e.g., psychopathy, narcissism, and antisocial values) and the use of alcohol and drugs.